RK ALGORITHM: STOCHASTIC PARALLEL METHODOLOGY FOR SYMMETRIC KEY CRYPTOGRAPHY - Ramesh, Yegireddi; Reddi, Kiran Kumar (APTIKOM Journal on Computer Science and Information Technologies, 2017)
With the enormous growth in the Internet and network, data security has become an inevitable concern forany organization. From antecedent security has attracted considerable attention from network researchers. In thisperspective many possible fields of endeavour come to mind with many cryptographic algorithms in a broader way,each is highly worthy and lengthy. As society is moving towards digital information age we necessitate highlystandard algorithms which compute faster when data size is of wide range or scope. On survey, numerous sequentialapproaches carried out by symmetric key algorithms on 128 bits as block size are ascertained to be highly insecurable and resulting at a low speed. As in the course the commodities are immensely parallelized on multi coreprocessors to solve computational problems, in accordance with, propound parallel symmetric key based algorithmsto encrypt/decrypt large data for secure conveyance. The algorithm is aimed to prevail by considering 64 character(512 bits) plain text data, processed 16 characters separately by applying parallelism and finally combine each 16-character cipher data to form 64-character cipher text. The round function employed in the algorithm is verycomplex, on which improves efficacy.